Synthesis of BaWO4/NRGO–g-C3N4 nanocomposites with excellent multifunctional catalytic performance via microwave approach - Sadiq, M. Mohamed Jaffer; Shenoy, U. Sandhya; Bhat, D. Krishna (Frontiers of materials science, 2018)
Novel barium tungstate/nitrogen-doped reduced graphene oxide-graphitic carbon nitride (BaWO 4 /NRGO-g-C 3 N 4 ) nanocomposite has been synthesized by a simple one-pot microwave technique. The synthesized nanocomposites are well characterized by diffraction, microscopic and spectroscopic techniques to study its crystal structure, elemental composition, morphological features and optical properties. The material prepared is tested for its performance as an electrocatalyst, photocatalyst and reduction catalyst. The nanocomposite catalyzed the photodegradation of methylene blue (MB) dye in 120 min, reduction of 4-nitro phenol (4-NP) to 4-amino phenol (4-AP) in 60 s, showed an impressive Tafel slope of 62 mV/dec for hydrogen evolution reaction (HER). The observed results suggest that the nanocomposite acts as an efficient multifunctional catalyst. The reported approach provides fundamental insights which can be extended to other metal tungstate-based ternary composites for applications in the field of clean energy and environment in the future.